2009
DOI: 10.1007/s00701-009-0367-5
|View full text |Cite
|
Sign up to set email alerts
|

Atypic geniculate neuralgia: atypic anatomic correlation of cranial nerve roots and AICA

Abstract: Geniculate neuralgia is a rare cause of craniofacial pains. The anterior inferior cerebellar artery is the offending vessel which compress nervus intermedius in the patients with typical geniculate neuralgia. We report a patient whose pain was atypical for either geniculate neuralgia and trigeminal neuralgia. At operation the anterior inferior cerebellar artery was coursing with the nerves and was separated. After the decompression the pain resolved immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…5,9 The most common arteries reported are the AICA and the PICA. 6,12,14 In these case reports, MVD of the NI without sectioning was sufficient to produce pain relief. 10,11,17 Anatomically, NVC is most likely to occur proximally near the brainstem.…”
Section: Figmentioning
confidence: 75%
See 1 more Smart Citation
“…5,9 The most common arteries reported are the AICA and the PICA. 6,12,14 In these case reports, MVD of the NI without sectioning was sufficient to produce pain relief. 10,11,17 Anatomically, NVC is most likely to occur proximally near the brainstem.…”
Section: Figmentioning
confidence: 75%
“…There is no quintessential culprit artery causing compression of the nerve, although a number of cases of neurovascular compression (NVC) of the NI by the anterior inferior cerebellar artery (AICA) and posterior inferior cerebellar artery (PICA) have been reported. 2,3,6,9,11,17 In the remainder of cases, the vast majority, the etiology is unknown.…”
mentioning
confidence: 99%
“…Sakas et al, 9 Bellotti et al, 10 Younes et al 11 and Ozer et al 12 reported similar cases of geniculate neuralgia with suspected compression of nervus intermedius by the anterior inferior cerebellar artery. All patients underwent microvascular decompression of the compressed nervus intermedius, with long-term resolution of pain.…”
Section: Surgerymentioning
confidence: 92%
“…Therefore, 18 papers were included in the review. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] All reports directly related to geniculate neuralgia were classified as level 4 evidence, consisting of single case reports or small case series. There were two level 1 systematic reviews, which discussed the medical therapy of neuralgia.…”
Section: Methodsmentioning
confidence: 99%
“…The main advantage of this non-destructive treatment option is a lower risk of sensory deficits in the nervus intermedius domain, although, also in MVD alone, neurological deficits such as transient facial nerve palsy or partial hearing loss have been observed [5,12,14] . The main limitation in those cases reported in the literature as well as in the present case is the relatively short time of follow-up.…”
Section: Discussionmentioning
confidence: 99%